Online moving of Chinese boys’ love fans: A platform ecology perspective - Zhang, Lin (Sage, 2025)
This study examines the online moving of Chinese Boys’ Love (BL) fans through the lens of platform ecology, exploring how they navigate censorship and create opportunity spaces across multiple digital platforms. Employing mixed methods combining participant observation, in-depth interviews, and secondary data analysis, the research maps the complex tactics BL fans used to maintain their community and content in a restrictive digital environment. The findings reveal that fans move between commercial, fan-run, and outbound-link platforms, to access different types of content and spaces. By combining platform affordances, fans create opportunity spaces that fulfill their desires for BL content, demonstrating remarkable resilience in the face of increasing restrictions. The study contributes to both fan studies and platform studies by extending analyses beyond single-platform interactions and deepening the platform ecology heuristic. It highlights the importance of cross-platform mobility in equipping fan communities to withstand structural vulnerabilities imposed by censorship and platform governance. The research also integrates political-economic analysis with ecological thinking, balancing considerations of user agency and power imbalances.